2014
DOI: 10.1007/s00394-014-0798-5
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean diet during pregnancy and serum lipid, lipoprotein and homocysteine concentrations at birth

Abstract: Neonates whose mothers consumed low MDA diets presented impaired lipoprotein and increased homocysteine levels at birth. A follow-up study on early cardiovascular disease prevention is needed to understand the importance of present findings later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…In a cross-sectional study, Gesteiro et al [76] analysed the MD adherence in 35 Spanish women during the first trimester of pregnancy, who completed 169-items FFQ guided by a trained dietician. Adherence to the MD was calculated with a modified version of the score used in the PREDIMED study [72].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional study, Gesteiro et al [76] analysed the MD adherence in 35 Spanish women during the first trimester of pregnancy, who completed 169-items FFQ guided by a trained dietician. Adherence to the MD was calculated with a modified version of the score used in the PREDIMED study [72].…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence suggests these conditions have their roots in utero as maternal obesity, dyslipidaemia, and hyperglycaemia are associated with child cardiometabolic health and developing insulin resistance and obesity later in life [85,86]. Although studies considered in this review indicate that higher adherence to the MD during pregnancy is a potential protective factor against abdominal obesity [73,74] and positively influences lipoprotein and homocysteine concentration [76], and insulin resistance in new-borns [70], the use of different endpoints to evaluate outcomes reduces the level of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis on the protective effects of the MD against non-communicable diseases (NCD) and for mental health benefits [ 72 , 73 ] would likely be beneficial in its promotion. Interestingly, although the health benefits of an MD were enabling factors, the reported benefits in preconception and pregnancy [ 26 , 27 , 28 , 29 , 30 , 31 , 74 , 75 , 76 ] were considered less important. Most participants indicated that the possibility of pregnancy was too far in the future to contemplate following a dietary pattern for benefits, and diet would not even be a concern in some participants unless there was difficulty in conception.…”
Section: Discussionmentioning
confidence: 99%
“…The MD has been shown to prevent diseases associated with chronic inflammation, including coronary heart disease and stroke, type 2 diabetes, cognitive diseases, and obesity [ 25 ]. In addition, research has also demonstrated numerous benefits to the preconception and pregnancy periods, such as a reduced risk of hypertensive disorders [ 26 ], reduced risk of GDM [ 27 ], improvement in glucose tolerance [ 28 ], reduced gestational weight gain [ 29 ], reduction in depressive symptoms and risk of postnatal depression [ 30 ], and improved offspring homocysteine and lipoprotein levels [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that adherence to a Mediterranean diet is associated with more favorable metabolic health in both the mother and infant, including lower risk for gestational diabetes and low birth weight, as well as lower neonatal insulin, blood glucose, lipids and lipoprotein. 64 67 These studies demonstrate that a positive intrauterine environment can improve maternal and neonatal outcomes and should be considered for public health recommendations and translation into clinical practice. However, to date, research on modifying maternal diet during pregnancy has primarily been confined to studies using animal models.…”
Section: Discussionmentioning
confidence: 89%